KONGLISH BORROWING TRANSLATION IN KOREAN “SWEET & SOUR” MOVIE - Rita Hartati; Stevany Silaban; Wildina Theressa (Universitas Negeri Medan, 2023)
Konglish is a Korean vocabulary adapted from English but pronounced according to Korean pronunciation. The pronunciation usually seems to sound like Korean, but the writing is more towards spelled English. An example is